1999
DOI: 10.1111/j.1469-7793.1999.0401p.x
|View full text |Cite
|
Sign up to set email alerts
|

The erg‐like potassium current in rat lactotrophs

Abstract: In rat lactotrophs from primary culture an inward-rectifying K¤ current is present which is characterized by sustained inward currents at membrane potentials more positive than −50 mV and by transient K¤ currents at more negative membrane potentials, when measured in high KCl external solution (Corrette et al. 1996). This current is similar to the inward-rectifying K¤ current (IK,IR) in clonal rat pituitary cells (GH×ÏBÜ cells;Bauer et al. 1990). However, in contrast to GH×ÏBÜ cells, the time course of current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
121
1
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(131 citation statements)
references
References 42 publications
8
121
1
1
Order By: Relevance
“…One component is an inwardly-rectifying K ϩ current (I K(IR) ) which exhibits the voltage-dependent activation and current decay during the hyperpolarizing pulses, whereas the other component is a sustained inward current which can be activated at potentials equal or positive to Ϫ50 mV. Consistent with a previous report (Schäfer et al 1999), this study demonstrates that like E-4031, risperidone is capable of blocking I K(IR) with an IC 50 value of 1 M, whereas the sustained inward component was not affected by risperidone.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…One component is an inwardly-rectifying K ϩ current (I K(IR) ) which exhibits the voltage-dependent activation and current decay during the hyperpolarizing pulses, whereas the other component is a sustained inward current which can be activated at potentials equal or positive to Ϫ50 mV. Consistent with a previous report (Schäfer et al 1999), this study demonstrates that like E-4031, risperidone is capable of blocking I K(IR) with an IC 50 value of 1 M, whereas the sustained inward component was not affected by risperidone.…”
Section: Discussionsupporting
confidence: 91%
“…Pituitary GH 3 lactotrophs, in addition to the presence of voltage-dependent K ϩ and Ca 2 ϩ currents, have been found to exhibit the inwardly rectifying K ϩ current (I K(IR) ) (Bauer et al 1990;Wu et al 1998) which, on the basis of biophysical and pharmacological properties, was identified as an erg -mediated K ϩ current (Schäfer et al 1999;Schwarz and Bauer 1999). This current was sensitive to caffeine, thyrotropin-releasing hormone, and class III antiarrhythmic agents (e.g., E-4031), and proposed to be an important determinant of the resting membrane potential (Bauer et al 1990;Barros et al 1994Barros et al , 1996Barros et al , 1997Weinsberg et al 1997;Bauer 1998;Schwarz and Bauer 1999).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These features of HERG channel dictate its role in repolarization of the cardiac action potential and frequency-dependent modulation of the action potential duration (11). Recent studies also suggest that an inwardly rectifying K ϩ conductance that is active near the resting membrane potential of gastrointestinal smooth muscle cells (12,13), pituitary cells (14 -16), carotid body (15)(16)(17), and microglia (18) has properties similar to that of HERG channels. In these cells HERG conductance has been directly demonstrated in single cells, and in esophageal and stomach smooth muscle the presence of a "window" current within the range of the resting potential and depolarization and contraction by HERG channel blockers of whole tissue segments strongly suggest a role for ether-a-gogo-related gene K ϩ conductance in maintaining resting membrane potential (12).…”
Section: From the Department Of Physiology University Of Oklahoma Hementioning
confidence: 99%
“…Members of the KCNH family share relatively close sequence homology but differ in the voltage dependence and kinetics of channel gating. The resulting diversity in current phenotype allows KCNH family members to perform a diverse range of physiological roles in the heart, during neuronal action potential firing (2), during phasic contraction in a range of smooth muscles (3,4), in hormone secretion (5)(6)(7), and in cell proliferation (8).…”
mentioning
confidence: 99%